Intra-channel stent release technique for fluoroless endoscopic ultrasound-guided lumen-apposing metal stent placement: changing the paradigm - Anderloni, Andrea; Attili, Fabia; Carrara, Silvia; Galasso, Domenico; Di Leo, Milena; Costamagna, Guido; Repici, Alessandro; Kunda, Rastislav; Larghi, Alberto (Endoscopy International Open, 2017)
Background Recently, a novel lumen-apposing fully covered self-expanding metal stent (LA-FCSEMS) mounted on an electrocautery-enhanced delivery system has been developed to perform endoscopic ultrasound (EUS)-guided transluminal drainage. From early experience, however, release of the proximal flange of the stent has mostly been done using endoscopic view guidance to ensure proper positioning.Aim We describe a new technique that we have named the Intra-Channel Stent Release Technique (ICSRT) to perform stent placement under complete EUS control, without the use of either fluoroscopic or endoscopic views.Material and methods Data on all consecutive patients who underwent EUS-guided drainage using the new ICSRT between June 2014 and April 2016 were retrospectively retrieved from two institution databases. All EUS procedures were performed by experienced endoscopists with the patient under conscious or deep sedation. The total procedure and stent deployment time, and adverse events related to stent positioning with the ICSRT were evaluated.Results One hundred consecutive patients (51 women; mean age ± SD, 66 ± 15.2 years, range 34 – 95) underwent EUS-guided transluminal drainage with the Hot AXIOS™ device using the new ICSRT. The procedure was technically successful in all but one patient (1 %). The mean total procedural time was 21.9 minutes (range 7 – 50), while the mean time for stent placement was 3.2 minutes (range 1 – 15). No major adverse events occurred.Discussion The ICSRT has been used to deploy the newly developed lumen-apposing FCSEMS under complete EUS guidance without fluoroscopic and/or endoscopic assistance. The technique appears to be safe and highly effective and should be learned by all interventional endosonographers in order to be able to perform drainage in all clinical scenarios.